(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article completes modern Ukrainian Goethean with historical-literature interpretation of a separate episode of J.W. Goethe biography. It deals with the analysis of interpretations and comments of famous scholars of the episode of the first meeting of J.W. Goethe and J. G. Herder depicted in „Poetry and Truth”. The influence of J.G. Herder on the formation of literature-critical views is underlined.